Export cartel exemptions: an International Political Economy approach - ARCHER, Caroline T. T. B. (2025)
This article analyzes trends related to legal exemptions for export cartels in the context of international trade and competition policies at a national level, with particular focus in the period from 1994 to 2004. Through the analysis of these trends, we seek to understand what makes countries change their export cartels regulations, starting from the initial hypothesis that the main factor influencing changes in these domestic policies is the international pressure exerted by countries potentially affected by the actions of an export cartel. We seek to verify this hypothesis through: (i) the analysis of export cartels under an International Political Economy (IPE) perspective and, more specifically, the Open Economy Politics (OEP) paradigm, aiming to identify, in theory, the elements that could influence the decision of a country to alter its export cartel exemptions; and, complementarily, (ii) a comparative analysis between five selected countries that were a part of the abovementioned trends Germany, South Korea, the UK, Japan and the USA to verify if the identified elements are present in practice. Thus, the article shifts the focus from the question that oriented many of the prior discussions i.e. which is the optimal way to regulate export cartels internationally? and strives to contribute to the debate by providing further information as to why significant changes have not been enacted and we remain with what has been perceived as a suboptimal regulation for export cartels, despite the issues previously voiced by government authorities, international organizations and scholars alike.